Teacher Interaction: A Qualitative Analysis Study in Assessment Learning - Fikri Maulana; Anggi Setia Lengkana; Encep Sudirjo (JUARA : Jurnal Olahraga, 2022)
This study aimed to determine the barriers to communication and instruction in physical education learning in the lower grades. This research method is qualitative, with a research design using a naturalistic inquiry paradigm. In this case, the obstacles analyzed are the obstacles to the interaction of elementary school physical education teachers with the learning of low-grade physical education teachers. Interviews, observations and documentation are used for data collection. As well as using source triangulation as the validity of research results. The results explained the perception of teachers and principals of the problem, namely the interaction of the teacher. The interview results emphasized;1) interaction, 2) type of communication, 3) approach, 4) strategy, 5) use of language, 6) gestures, 7) compound intelligence, 8) teacher difficulty, 9) increased interaction, and 10) physical education learning. This research proves that communication barriers and instructions regarding the interaction of PJOK teachers in the learning of adolescents in the lower grades are said to have sufficient obstacles in their application, as well as how to overcome the challenges. This can be proven from the teacher's perception of the way of communication and the instructions presented, although there are still limitations regarding small data sources. It will be a record for further research, i.e. the use of different methods.